Increased Variability in Tacting Under a Lag 3 Schedule of Reinforcement - Heldt, Juliane (The Society for the Experimental Analysis of Behavior, Inc, 2012)
Research has shown that variability may be an operant dimension of behavior. One method of reinforcing response variability is to use a lag schedule of reinforcement (Page & Neuringer, 1985). Several studies have shown that a Lag 1 schedule is effective in increasing variable responding with human participants (e.g., Esch, Esch, & Love, 2009; Lee, McComas, & Jawor, 2002). In these arrangements, however, the return to baseline responding during reversal phases suggests that the resulting behavior change may not be maintained following intervention. The purpose of the present study was to investigate the effects of a Lag 3 schedule on increasing and maintaining variability of tacts in 2 children diagnosed with developmental disabilities. Results demonstrated increased variability in tacting for both participants and maintenance in variable responding after a 3-week follow-up.